Peningkatan Ekspresi PD-L1 pada Squamous Cell Carcinoma Nasofaring Tipe Undifferentiated Non Keratinizing - Yusuf, Franky; Prasetyo, Awal; Karlowee, Vega; Astuti, Meira Dewi Kusuma; Nur, Rizki Widya (RSUP Dr. Kariadi, 2021)
Increased Expression of PD-L1 in Undifferentiated Non Keratinizing Squamous Cell Carcinoma Nasopharynx ABSTRACT BACKGROUND: PD-L1 expressed by tumor cells in nasopharyngeal carcinoma (NPC) can be used by tumor cells to avoid the patient's immune system. This can affect prognosis such as age, gender, histopathological type, tumor stage and quality of life through immunosuppressive activity. PD-L1 expression is expected to be a biomarker for prognostic factor assessment and immunotherapy. OBJECTIVE: To determine whether there is a relationship between the level of PD-L1 expression and prognostic factors in NPC. METHODS: This is analytic observational study with a cross-sectional design. PD-L1 expression was examined immunohistochemically using 61 samples of paraffin block, which had been diagnosed as NPC in the Laboratory of Anatomical Pathology, Dr. Kariadi from January 2017 to June 2020. Patient clinical data were used as prognostic factors, namely age, gender, histopathological type, tumor stage and quality of life. Analysis was performed with the Chi-Square test to determine the relationship between the level of PD-L1 expression and prognostic factors. RESULTS: There was a significant correlation between PD-L1expression in tumor cells and histopathological type (p=0.001). No significant correlation between PD-L1 expression and age (p=0.405), gender (p=0.241), tumor stage (p=0.928) and quality of life (p=0.103). CONCLUSION: PD-L1 expression in this study cannot be used as a prognostic factor in NPC patients, although the histopathological type shows a significant relationship, so further research is needed with a larger sample and a longer period. Keywords: Nasopharyngeal carcinoma; PD-L1; prognostic factor